ASPECTS OF SUSTAINABLE CONSUMPITION: A COMPARATIVE STUDY OF CONSUMES WITH FORMAL EDUCTION IN THE ENVIRONMENTAL AND CONSUMERS IN GENERAL - Burguesi Pacheco, Paulo Henrique; Ribeiro da Silva, Hermes Moretti [UNESP]; Spers, Eduardo Eugenio; Hamza, Kavita Miadaira (Univ Feevale, Inst Ciencias Sociais Aplicadasicsa, 2019)
The practice of sustainable consumption has been discussed by instituitions, governmentes and experts, who defend that change in this form of consumption can help minimize some of the problems of evironmental degradation problems. Some studies indicate that more and more consumers seek to consume in a sustainable way, but there are still studies that compare groups with different characteristics in order to verify if such differences influence their behaviors. In this sense, this research was based on the scale of sustainable consumption proposed by Ribeiro and Veiga (2011) and applied with two groups of consumers, the first one being composed of 172 people with some knowledge of environmental causes and the second group of 210 people without proof of knowledge in the area. The results indicated that there is a trend towards sustainable consumption between both groups of consumers, but the level of engagement among people inserted in environmental areas has shown to be much higher than people without this environmental bias.
Keywords: Sustainable consumption; Consumer behavior; Sustainability